Fostering Innovation in the Restaurant Industry: The Impact of Leadership Styles on Employee Creativity in Jakarta and Tangerang - Aristoa, Benny; Abelael, Timothy Ethan (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
This research explores the influence of leadership styles””specifically transactional, transformational, and laissez-faire””on innovative work behavior within the bustling restaurant industry of Jakarta and Tangerang, vital components of Indonesia's economic landscape. Utilizing a survey methodology that engaged 200 employees from full-service restaurants and adopting the Multifactor Leadership Questionnaire (MLQ) for evaluating the impact of leadership styles on innovation, the study employs SMART PLS4 for thorough data analysis. The findings reveal a dichotomy in the effects of leadership styles on innovation: transactional leadership, with its focus on reward and performance, negatively impacts innovative behavior, suggesting that a strict emphasis on outcomes may deter creative initiatives. Conversely, transformational leadership, characterized by its motivational and intellectually stimulating approach, significantly fosters innovation, encouraging employees to surpass routine expectations and engage in creative problem-solving. Laissez-faire leadership, marked by a lack of active involvement, similarly detracts from innovation, failing to provide the necessary guidance and encouragement for creative endeavors. The research underscores transformational leadership as the most effective style for promoting innovation in the restaurant sector, advising managers to adopt practices that inspire and challenge employees to ensure a competitive edge in the dynamic F&B industry.